2021
DOI: 10.3390/jpm11080782
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptomic Analysis of Head and Neck Squamous Cell Carcinomas for Prognostic Indications

Abstract: Survival analysis of the Cancer Genome Atlas (TCGA) dataset is a well-known method for discovering gene expression-based prognostic biomarkers of head and neck squamous cell carcinoma (HNSCC). A cutoff point is usually used in survival analysis for patient dichotomization when using continuous gene expression values. There is some optimization software for cutoff determination. However, the software’s predetermined cutoffs are usually set at the medians or quantiles of gene expression values. There are also fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 115 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…Recent studies have found that FCGBP is expressed in 33 carcinomas compared with surrounding normal tissues (66). Moreover, it is significantly highly expressed in invasive breast carcinoma, diffuse large B-cell lymphoma, glioblastoma multiforme, lung adenocarcinoma, pancreatic adenocarcinoma, rectal adenocarcinoma, ovarian carcinoma, lower grade glioma, gastric cancer, and Human Papillomavirus (HPV)-infected patients with head and neck squamous cell carcinoma (HNSCC) (66)(67)(68)(69). Of these, the overexpression of this molecule usually predicts poor prognosis in ovarian carcinoma and lower-grade glioma (67).…”
Section: Iggfc-binding Protein As a Biomarker For Cancer Treatment An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found that FCGBP is expressed in 33 carcinomas compared with surrounding normal tissues (66). Moreover, it is significantly highly expressed in invasive breast carcinoma, diffuse large B-cell lymphoma, glioblastoma multiforme, lung adenocarcinoma, pancreatic adenocarcinoma, rectal adenocarcinoma, ovarian carcinoma, lower grade glioma, gastric cancer, and Human Papillomavirus (HPV)-infected patients with head and neck squamous cell carcinoma (HNSCC) (66)(67)(68)(69). Of these, the overexpression of this molecule usually predicts poor prognosis in ovarian carcinoma and lower-grade glioma (67).…”
Section: Iggfc-binding Protein As a Biomarker For Cancer Treatment An...mentioning
confidence: 99%
“…Thus, Stranik speculates that FCGBP may be used as a novel diagnostic marker for intraamniotic infection in the two forms of natural preterm births (10). In contrast, a significant downregulation of FCGBP is found in adrenocortical carcinoma, chromophobe kidney cancer, clear cell kidney carcinoma, HNSCC and rectum adenocarcinoma, and cutaneous skin melanoma (66)(67)(68). Similarly, the expression of FCGBP is downregulated in colon cancer than that of surrounding normal tissues.…”
Section: Iggfc-binding Protein As a Biomarker For Cancer Treatment An...mentioning
confidence: 99%
“…For all patients the ability to identify residual disease and discriminate between responders and non-responders would greatly enhance treatment effectiveness. Recent work has revealed several potential molecular markers of aggressive SCCs, including nucleic acids [ 42 , 43 , 44 ], and proteins [ 45 , 46 ]. Notably, recent analysis of data generated by transcriptome analysis [e.g., The Cancer Genome Atlas (TCGA) Research Network, (accessed on 9 September 2022)] [ 47 ], as well as a growing body of work in related preclinical (cell culture & animal) models, strongly suggests that the specific and differential expression of chondroitin sulfate (CS) proteoglycan 4 (CSPG4) may be used a potential marker of clinical course in SCCs.…”
Section: Need For Markers Of Malignant Sccmentioning
confidence: 99%
“…To compare expression between cancer and control (noncancer) tissues one-way ANOVA was used (α = 0.05). Transcriptome data from recent public data on RDEB SCCs and cell lines was also reanalysed [ 43 , 44 ], using nonparametric Mann–Whitney U analysis (α = 0.05), to compare medians (α = 0.05). Survival analysis was conducted using Kaplan–Meier survival (α = 0.05), and comparison of tumour stage using one-way ANOVA (α = 0.05).…”
Section: Cspg4 Expression In Disease and Developmentmentioning
confidence: 99%
“…For all patients the ability to identify residual disease and discriminate between responders and non-responders would greatly enhance treatment effectiveness. Recent work has revealed several potential molecular markers of aggressive SCCs, including nucleic acids [42][43][44], and proteins [45,46]. Notably, recent analysis of data generated by transcriptome analysis [e.g., The Cancer Genome Atlas (TCGA) Research Network (www.cancer.gov/tcga)] [47], as well as a growing body of work in related preclinical (cell culture & animal) models, strongly suggests that the specific and differential expression of chondroitin sulfate (CS) proteoglycan 4 (CSPG4) may be used a potential marker of clinical course in SCCs.…”
Section: Need For Markers Of Malignant Sccmentioning
confidence: 99%